2002
DOI: 10.1016/s0020-1693(02)00962-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding patterns of 7,9-dimethylguanine and its transplatinum(II) complexes

Abstract: Methylation at the N7 position is one of the most frequently naturally occurring modifications of guanosine. This alteration drastically changes the hydrogen bonding and acid–base properties of the guanine nucleobase. Here we show on the example of the model nucleobase 7,9-dimethylguanine that due to blockage of N7 of the purine ring, new hydrogen bonding patterns occur on the minor groove binding face of this nucleobase involving the ring nitrogen N3 and the exocyclic amino group N2H2. The free 7,9-dimethylgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 130 publications
0
5
0
Order By: Relevance
“…All these geometric details make this fragment of the imidazole ring more regular in (II) than in (I). The N7-C8 and N9-C8 bond lengths are also unequal in the recently reported 7,9-dimethylpurinium salts (Hocek et al, 2005;Nasiri et al, 2005;Sigel et al, 2002) represented by structures (III)-(V), respectively (the differences in N-C bond lengths are in the range 0.016-0.025 Å ). As the N7-C8 bond is shorter by 0.017 Å in salt (II), double-bond character can be assigned to this bond and the resonance structure is represented by formula (IIB).…”
Section: Commentmentioning
confidence: 79%
See 1 more Smart Citation
“…All these geometric details make this fragment of the imidazole ring more regular in (II) than in (I). The N7-C8 and N9-C8 bond lengths are also unequal in the recently reported 7,9-dimethylpurinium salts (Hocek et al, 2005;Nasiri et al, 2005;Sigel et al, 2002) represented by structures (III)-(V), respectively (the differences in N-C bond lengths are in the range 0.016-0.025 Å ). As the N7-C8 bond is shorter by 0.017 Å in salt (II), double-bond character can be assigned to this bond and the resonance structure is represented by formula (IIB).…”
Section: Commentmentioning
confidence: 79%
“…Recently, the structures of a few 7,9-dialkylpurinium salts (where the anion is iodide, bromide or perchlorate) have been analyzed (Sigel et al, 2002;Nasiri et al, 2005;Hocek et al, 2005;Fu & Lam, 2005;Torii et al, 2006). We have now determined the crystal structure of 2,6-dimethoxy-7,9dimethylpurinium iodide as its hemihydrate, (II), to obtain information about the positions and conformations of the methoxy groups and the geometry of the imidazole ring in comparison with (I) (Kowalska et al, 1999) in an attempt to explain some results of the internal thermal O-N and N-N migrations of the alkyl groups (Kowalska & Maślankiewicz, 1997).…”
Section: Commentmentioning
confidence: 99%
“…However, studies have shown that due to blockage of N7 of the purine ring, the same hydrogen bonding patterns occur on the minor groove binding face in this nucleobase ( Sigel et al, 2002 ). To further demonstrate the universality of this strategy, we chose bpda (11.2 Å) with larger molecular length as the bridging ligand, and fortunately obtained the single crystal structure of 4.…”
Section: Resultsmentioning
confidence: 99%
“…7,9-Dimethylguanine is a rare nucleobase in the cap of message RNA (mRNA) and transfer RNA (tRNA) [26,27] 7,9-Dimethylguanine is converted from N 7 -methylguanine [28], which has various functions in an organism. N 7 -Methylguanine in the 5' cap of mature mRNAs mediates cap-related biological functions and functions as an identifier of self RNA in the innate immune system, then ensures cap-dependent protein synthesis [29].…”
Section: Discussionmentioning
confidence: 99%